2019
DOI: 10.1139/bcb-2018-0384
|View full text |Cite
|
Sign up to set email alerts
|

IM-12 activates the Wnt–β-catenin signaling pathway and attenuates rtPA-induced hemorrhagic transformation in rats after acute ischemic stroke

Abstract: Hemorrhagic transformation (HT) is a devastating complication for patients with acute ischemic stroke (AIS) who are treated with tissue plasminogen activator (tPA). HT is associated with high morbidity and mortality, but no effective treatments are currently available to reduce the risk of HT. Therefore, methods to prevent HT are urgently needed. In this study, we used IM-12, an inhibitor of glycogen synthase kinase 3β (GSK-3β), to evaluate the role of the Wnt–β-catenin signaling pathway in recombinant tPA (rt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Given that upregulating endothelial Wnt/β‐cat has been demonstrated as a novel potential treatment for BBB protection following ischemic stroke, 10 , 11 , 12 , 13 we wondered if the treatment after ischemic stroke would induce any changes of non‐canonical Wnt signalings. The mice with endothelial β‐catenin constitutive activation were generated, shown in Figure 3A .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that upregulating endothelial Wnt/β‐cat has been demonstrated as a novel potential treatment for BBB protection following ischemic stroke, 10 , 11 , 12 , 13 we wondered if the treatment after ischemic stroke would induce any changes of non‐canonical Wnt signalings. The mice with endothelial β‐catenin constitutive activation were generated, shown in Figure 3A .…”
Section: Resultsmentioning
confidence: 99%
“…(2) Previous studies have shown that Wnt/β‐cat, Wnt/PCP, and Wnt/Ca 2+ signalings collectively contribute to the endothelial growth, angiogenesis, and BBB formation, 1 , 2 , 6 , 7 while the antagonisms between canonical (Wnt/β‐cat) and non‐canonical (Wnt/PCP and Wnt/Ca 2+ ) signalings in physiological status have been implicated. 8 , 9 Given that it has been reported that Wnt/β‐cat signaling augmentation could protect BBB after cerebral I/R, 10 , 11 , 12 if upregulating Wnt/β‐cat signaling could affect Wnt/PCP and Wnt/Ca 2+ signalings becomes a new question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silencing of the Wnt/β-catenin pathway contributes to the development of ischemic stroke [28]. Activation of Wnt/β-catenin signaling contributes to the reduction of neuroinflammation, attenuation of BBB disruption, and facilitation of neurological recovery [29,30]. A previous study found that DANCR activated Wnt/βcatenin signaling to promote glioma proliferation [13].…”
Section: Agingmentioning
confidence: 99%
“…Recently, we demonstrated that following acute cerebral ischemia/reperfusion injury in mice, decreased canonical Wnt signaling activity in Gpr124 knockout brain endothelium led to exacerbation of BBB disruption and severe ICH, resembling severe PH in human strokes 21 . Furthermore, canonical Wnt signaling activity regulated rt‐PA‐induced HT in rodent ischemic stroke models 44‐46 . Nevertheless, the impact of canonical Wnt signaling pathway on human BBB integrity and HT after ischemic stroke remains completely unexplored.…”
Section: Introductionmentioning
confidence: 99%